Seismic characteristics of unreinforced mud masonry houses in Nepal: A miserable scenario before and after 2015 Gorkha (Nepal) earthquake. (June 2021) - Khadka, Binod; Shakya, Manjip
Highlights: Traditional construction technology of local masonry houses in Nepal. Condition of mud bonded masonry houses both before and after 2015 Gorkha earthquake. Haphazard modification of old house and lack of maintenance common in historic cities. Miserable damage scenario and various form of failure mechanism in masonry houses. Long history of earthquake damages in Nepal shows immediate need of earthquake resistant construction practices. Abstract: The new methodology and technology introduced for sustainable improvement of structural characteristics may play an adverse effect unless the ways of the past are well understood. Hence, analyzing past construction technology is always necessary for future intervention to any structure. A detailed study (inspecting numerous unreinforced mud bonded masonry houses, questionnaire, and discussion with technical and local people) carried out for nearly 8 years (starting from early 2012) in different regions of Nepal, both before and after Mw 7.8 2015 Gorkha earthquake showed the miserable housing scenario. Our past construction practice was non-engineered due to lack of knowledge and technology regarding seismic-resistant construction technology. Different regions in Nepal adopted their own construction techniques, neglecting the minimal design criteria for safer earthquake-resistant building construction. This paper is basically focused on correlating the construction characteristics of mud masonry houses with seismic characteristics. Detail information about common construction practices, the comparative status of masonry houses both before and after the 2015 earthquake, related damage mechanisms, and recommendation provided to prepare structures for upcoming hazards has contributed in highlighting the importance of this study. Furthermore, the results of the rapid visual assessment are justified by photographs taken before and after the recent 2015 earthquake.